Використання математичного сподівання для швидкого центрування наборів зображень - Пелешко, Д.Д. (Моделювання та інформаційні технології, 2009)
There is proposed RSA algorithm modification on the based of the form of pixel threads. The used picture must be in the one byte pixel format and allows contour separation.